Atividade antifúngica do óleo essencial de origanum vulgare l. (orégano) e do carvacrol, sobre cepas de cryptococcus neoformans - Bezerra, André Parente de Brito (2017)
Cryptococcosis is an infection caused by fungus of the genus Cryptococcus. This fungus is cosmopolitan and there are two main species, Cryptococcus neoformans and Cryptococcus gatii. The infection manifests primarily non-lung tissue and central nervous system, being highly lethal when not treated properly. Individuals with HIV or the compromised immune system are more susceptible to the development of cryptococcosis. Therapeutic agents available for the treatment of cryptococcosis are limited and toxic, besides the high incidence of physical resistance to these agents. Therefore, a search for other therapeutic alternatives for the treatment of cryptococcosis is essential. In this scenario, natural products, such as essential oils and their phytochemicals, are very promising for the development of new antifungal drugs. The objective of this study was to evaluate the antifungal activity of O. vulgare L. (oregano) and its major phytochemical, carvacrol, on Cryptococcus neoformans strains. The composition of the essential oil was analyzed by Gas Chromatography coupled to Mass Spectrometry (GC-MS). Minimum Inhibitory Concentration (MIC) and Minimum Fungicidal Concentration (CFM) were determined by broth microdilution technique. The sensitivity profile of the strains was determined by disc diffusion method, as well as the study of association of the products with antifungals. The kinetics of microbial death were also evaluated. The results of CG-MS have indicated a higher concentration of carvacrol (67.97%), p-cymene (11.67%), γ-terpinene (7.92%), thymol (7.84%) and linalool 3.44%). The MIC50, as well as MIC90, of the essential oil were 64 μg/mL. Carvacrol presented MICs of 32 μg/mL and MICs of 64 μg/mL. The CFM50 and CFM90 from the essential oil were 64 μg/mL and 256 μg/mL respectively. Carvacrol has shown CFM50 equal to 32 μg/mL and CFM90 equal to 64 μg/mL. The strains profile has shown 100% of sensitivity to amphotericin B (100 μg), 30% sensitivity to fluconazole (25 μg) and any strain has shown sensitivity to 5-fluorocytosine (10 μg). The association of essential oil and carvacrol with amphotericin B and fluconazole has not shown synergism of action. The microbial death curve has shown that the products have concentration-dependent fungicidal effect. The results of the study demonstrate that the essential oil of oregano and carvacrol have an antifungal activity, showing them as promising agents to the development of drugs capable to treat cryptococcosis.